2009
DOI: 10.1093/nar/gkn848
|View full text |Cite
|
Sign up to set email alerts
|

SysPIMP: the web-based systematical platform for identifying human disease-related mutated sequences from mass spectrometry

Abstract: Some mutations resulting in protein sequence change might be tightly related to certain human diseases by affecting its roles, such as sickle cell anemia. Until now several databases, such as PMD, OMIM and HGMD, have been developed, providing useful information about human disease-related mutation. Tandem mass spectrometry (MS) has been used for characterizing proteins in various conditions; however, there is no system in place for finding disease-related mutated proteins within the MS results. Here, a Systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
(52 reference statements)
0
14
0
1
Order By: Relevance
“…As an example, pull-down experiments in human tumor samples demonstrated that interactions between the oncoprotein MDM2 and the ribosomal protein L11 can be disrupted by missense mutations in MDM2, which help retain MDM2's full p53-suppressive function while escaping inhibition by L11 [Lindstrom, et al, 2007]. As another example, shotgun proteomics data analysis usually relies on database search and adding protein mutation information into the database can help identify mutated proteins [Schandorff, et al, 2007; Xi, et al, 2009]. …”
Section: Discussionmentioning
confidence: 99%
“…As an example, pull-down experiments in human tumor samples demonstrated that interactions between the oncoprotein MDM2 and the ribosomal protein L11 can be disrupted by missense mutations in MDM2, which help retain MDM2's full p53-suppressive function while escaping inhibition by L11 [Lindstrom, et al, 2007]. As another example, shotgun proteomics data analysis usually relies on database search and adding protein mutation information into the database can help identify mutated proteins [Schandorff, et al, 2007; Xi, et al, 2009]. …”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we employed an integrated genomics and proteomics strategy to create a Human Protein Mutant Database (HPMD), against which experimentallyderived secretome peptide spectra were searched. HPMD was created using publicly available datasets of known functional mutations (31,479) and SNPs (140,440 mutations) from UniProt [51], Protein Mutation Database, OMIM and SysPIMP [52]. Using iMASp, we detected 112 putative mutated tryptic peptides (corresponding to 57 proteins) from a panel of 18 human CRC cell line secretome data.…”
Section: Mutant Proteins As Biomarkersmentioning
confidence: 99%
“…Although it is not included in each record, an important part of many OMIM records is the ALLELIC VARIANTS (AV) section, which primarily describes disease-producing mutations (Xi et al, 2009). The Entrez Programming Utilities (eUtils) provide a stable Entrez query and database system interface (Wheeler et al, 2007).…”
Section: Introductionmentioning
confidence: 99%